Analisis Kaidah Universalitas dan Historisitas Teks Agama, dan Implementasinya dalam Ahkam Al-Usrah - Ahmad Zuhairuz Zaman (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
This study discusses two rules that attract each other in an effort to understand the meaning behind the text of law both in the form of verses and hadith. The two rules are the rule of "al-'ibrah bi 'umūm al-lafẓ lā bi khuṣūṣ al-sabab" and the rule of "al-'ibrah bi khuṣūṣ al-sabab lā bi' umūm al-laf̣̣ẓ " The result of this study is that generally, there are three cases studied by scholars associated with the universality and particularity of the text they nuzul or becauseWurud. First, when there is a qarīnah (correlative clue) that indicates the generality of the text, then the scholars agree that what is taken is the generality of the text. Second, when there is qarīnah siyāq which indicates the existence of specialization, then the scholars agree that the text is no longer general, but the text is pen-takhṣīṣ-an by qarīnah siyāq understood through the deepening of the relationship of text and because nuzul or becauseWurud. Third, when there is no qarīnah that points to generality or specificity, then this realm is still debatablegives among scholars andrise to dualism between the two rules above. And the opinion chosen by the majority of fuqahā ' is the first rule which is "al-'ibrah bi' umūm al-lafẓ lā bi khuṣūṣ al-sabab". Qualitative methods are used in writing this article in order to explore the rules related to the universality and historicity of a legal text. Keywords: becausenuzul, becauseWurud, 'Generalal-lafz, takhsis, siyāq